No degeneration found in focal cartilage defects evaluated with dGEMRIC at 12-year follow-up. (2nd January 2017) - Engen, Cathrine Nørstad; Løken, Sverre; Årøen, Asbjørn; Ho, Charles; Engebretsen, Lars
Abstract : Background and purpose — The natural history of focal cartilage defects (FCDs) is still unresolved, as is the long-term cartilage quality after cartilage surgery. It has been suggested that delayed gadolinium-enhanced magnetic resonance imaging of cartilage (dGEMRIC) is a biomarker of early OA. We aimed to quantitatively evaluate the articular cartilage in knees with FCDs, 12 years after arthroscopic diagnosis. Patients and methods — We included 21 patients from a cohort of patients with knee pain who underwent arthroscopy in 1999. Patients with a full-thickness cartilage defect, stable knees, and at least 50% of both their menisci intact at baseline were eligible. 10 patients had cartilage repair performed at baseline (microfracture or autologous chondrocyte implantation), whereas 11 patients had either no additional surgery or simple debridement performed. Mean follow-up time was 12 (10–13) years. The morphology and biochemical features were evaluated with dGEMRIC and T2 mapping. Standing radiographs for Kellgren and Lawrence (K&L) classification of osteoarthritis (OA) were obtained. Knee function was assessed with VAS, Tegner, Lysholm, and KOOS. Results — The dGEMRIC showed varying results but, overall, no increased degeneration of the injured knees. Degenerative changes (K&L above 0) were, however, evident in 13 of the 21 knees. Interpretation — The natural history of untreated FCDs shows large dGEMRIC variations, as does the knee articular cartilage of surgically treated patients. In this study, radiographic OA changes did not correlate with cartilage quality, as assessed with dGEMRIC.